Meningkatkan kemampuan siswa dalam menulis puisi bebas dengan model pembelajaran picture and picture dan concept sentence - K. Dasril (Indonesian Journal of Educational Development, 2021)
The purpose of this research is to find out the effectiveness and efficiency ofthe pictures and pictures and concept sentences learning models in improving the ability to write free verse poemin the class VIII-A students at SMP Negeri 8 Batanghari. The design in this research is an action research model. The form of action is performed in three cycles. Each cycle consists of planning, implementing actions, and evaluating/revising. This research took place from September to December 2019, during class hours, in the Language Laboratory of SMP Negeri 8 Batanghari, Wednesday at the 3rd and 4th hours (08.45 to 10.10 a.m). From the results of this research, it can be concluded that the combination of picture and picture and concept senten celearning models could improve the ability to write free verse poem in the class VIII-A students at SMP Negeri 8 Batanghari. Tujuan penelitian ini adalah untuk mengetahui efektivitas dan efesiensi model pembelajaran picture and picture dan concept sentence untuk meningkatkan kemampuan menulis puisi bebas pada siswa kelas VIII A SMP Negeri 8 Batanghari.Rancanagan penelitian ini berbentuk penelitian tindakan. Bentuk tindakannya dilaksanakan dalam tiga siklus. Setiap siklus terdiri atas tahap perencanaan, pelaksanaan tindakan, dan evaluasi/revisi. Penelitian ini berlangsung dari bulan September sampai dengan Desember 2019. Waktu pelaksanaan setiap jam pelajaran dan ruang Laboratorium Bahasa Indonesia SMP Negeri 8 Batanghari, Rabu jam ke 3 dan 4 (pukul 08.45 s.d. 10.10 WIB). Dari hasil penelitian dapat disimpulkan bahwa perpaduan model pembelajaran picture and picture dan concept sentence dapat meningkatkan kemampuan menulis puisi bebas siswa kelas VIII A SMP Negeri 8 Batanghari.